Journalism, revolutionary technologies and preventing future harm : proposing the flaming torch media ethics theory and the ten tenets field guide for responsible and ethical communication on science and technology’s cutting edge - Van Rooyen, Renier Stephanus (2022)
Thesis (DPhil)--Stellenbosch University, 2022.